1986
DOI: 10.1111/j.1530-0277.1986.tb05117.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chronic Ethanol Consumption on Salivary Gland Morphology and Function in the Rat

Abstract: Chronic ethanol consumption in rats resulted in a striking fat accumulation in the acinar cells of the parotid gland demonstrated by light microscopy. In addition, a significant decrease in parotid wet weight (p greater than 0.02) and in protein content of the gland (p greater than 0.02) was observed following alcohol feeding. Wet weight, protein content, and morphology of the submaxillar gland were not affected by ethanol feeding. Alcohol metabolism, similar to that found in the pancreas, via a cytosolic alco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0
4

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(33 citation statements)
references
References 16 publications
4
25
0
4
Order By: Relevance
“…Our findings agree with the alcohol-induced SF reduction observed in experimental studies [35]. Our results are also consistent with the study reported by Dutta et al [36], in which chronic alcohol intoxication resulted in a reduction in the stimulated SF from parotid glands.…”
Section: Discussionsupporting
confidence: 83%
“…Our findings agree with the alcohol-induced SF reduction observed in experimental studies [35]. Our results are also consistent with the study reported by Dutta et al [36], in which chronic alcohol intoxication resulted in a reduction in the stimulated SF from parotid glands.…”
Section: Discussionsupporting
confidence: 83%
“…Our results confirm the data in the literature [42,43], in which chronic alcohol consumption caused a reduction in SF. Morphological changes of salivary glands, such as those described above, are considered to be involved in SF reduction in people addicted to alcohol.…”
Section: Discussionsupporting
confidence: 83%
“…These results indicate a certain mutual effect between ethanol and oral microorganisms. Chronic alcohol consumption may increase bacterial concentrations through affecting salivary gland morphology and decreasing salivary flow (98,99).…”
Section: Interactions Between Alcohol Consumption and The Correspondimentioning
confidence: 99%